Ligand‐Centered Radical Activity by a Zinc‐Schiff‐Base Complex towards Catechol Oxidation. Issue 38 (16th October 2018) - Das, Subrata; Sahu, Amrita; Joshi, Mayank; Paul, Suvendu; Shit, Madhusudan; Roy Choudhury, Angshuman; Biswas, Bhaskar
Abstract: In this work, we present the synthesis and structural characterization of a new Zn(II)‐Schiff base complex, [Zn(L )(H2 O)] (1 ), [L = N, N′ ‐bis(3‐methoxysalicylidene)‐1, 3‐diamino‐2‐propanol]. Single crystal X‐ray structural analysis reveals that1 crystallizes in monoclinic system with P 21 /c space group. The compound shows good photo‐luminescence property in methanol medium. This Zn(II) complex has been evaluated as a catalytic system in the catalytic oxidation of 3, 5‐di‐ tert ‐butylcatechol (DTBC) in methanol. The Zn(II) complex displays good catecholase like activity with significant turn over, k cat (h –1 )=7.99×10 2 in methanol under aerobic condition. Very interestingly, we are able to isolate the oxidation product as 3, 5‐di‐ tert ‐butylquinone (2 ) in association with the substrate in the form of a single crystal. Electron paramagnetic resonance (EPR), electron spray ionization (ESI) mass and 1 H nuclear magnetic resonance (NMR) spectral analyses of the reaction mixture between Zn(II) complex and DTBC recommend that the course of catalysis proceeds through substrate‐catalyst adduct formation & confirm the presence of radical pathways in favour of oxidation products. The computation studies have been executed with density functional theory and all experimental observations are well rationalised with extensive theoretical calculations. Being a redox inactive metal ion, catalytic oxidation of DTBC by Zn(II) complexes will always be a remarkable example in the scientific community. Abstract : A new mononuclear zinc(II)‐Schiff base complex, [Zn(L)(H2 O)] (1 ) has been synthesized and structurally characterized through different analytical techniques in support with computational studies. This Zn(II) compound exhibited catalytic oxidation of 3, 5‐DTBC with a significant turn over number, 7.99×10 2 h −1 and recommended the radical pathways for the production of 3, 5‐DTBQ product.